Emotions, senses, spaces: Ethnographic engagements and intersections - Hemer, Susan R.; Dundon, Alison (The University of Adelaide Press, 2016)
This volume draws together three core concerns for the social sciences: the senses and embodiment, emotions, and space and place. In so doing, these collected essays consider the ways in which these core concerns are mutually constitutive. This includes how spaces evoke, constrain or are composed by the senses and emotions; the ways in which emotions are generated or transformed in certain spaces and through sensual engagement; and the processes by which embodied senses create spaces and emotions. The chapters engage with intersections between space, sense and emotion through a range of experiences and activities including dance, bullfights, healing ceremonies, celebrations and music. The authors herein critically examine diverse contexts, in and through which relations between sensate bodies, spaces and places, and emotions are constituted. The chapters draw on long-term ethnographic fieldwork from which the authors critically engage with their material on a fundamental level and contribute to contemporary debates about the nature and experience of emotions, the sensing body, and spaces and places.
Keywords: anthropologie; corps; discipline; ethnographie; genre; ressource en ligne; sciences humaines; thématiques; émotions